A Core–Shell Albumin Copolymer Nanotransporter for High Capacity Loading and Two‐Step Release of Doxorubicin with Enhanced Anti‐Leukemia Activity. Issue 6 (7th December 2012) - Wu, Yuzhou; Ihme, Susann; Feuring‐Buske, Michaela; Kuan, Seah Ling; Eisele, Klaus; Lamla, Markus; Wang, Yanran; Buske, Christian; Weil, Tanja
Abstract The native transportation protein serum albumin represents an attractive nano‐sized transporter for drug delivery applications due to its beneficial safety profile. Existing albumin‐based drug delivery systems are often limited by their low drug loading capacity as well as noticeable drug leakage into the blood circulation. Therefore, a unique albumin‐derived core‐shell doxorubicin (DOX) delivery system based on the protein denaturing‐backfolding strategy was developed. 28 DOX molecules were covalently conjugated to the albumin polypeptide backbone via an acid sensitive hydrazone linker. Polycationic and pegylated human serum albumin formed two non‐toxic and enzymatically degradable protection shells around the encapsulated DOX molecules. This core‐shell delivery system possesses notable advantages, including a high drug loading capacity critical for low administration doses, a two‐step drug release mechanism based on pH and the presence of proteases, an attractive biocompatibility and narrow size distribution inherited from the albumin backbone, as well as fast cellular uptake and masking of epitopes due to a high degree of pegylation. The IC50 of these nanoscopic onion‐type micelles was found in the low nanomolar range for Hela cells as well as leukemia cell lines. In vivo data indicate its attractive potential as anti‐leukemia treatment suggesting its promising profile as nanomedicine drug delivery system.